Reimagining the Langkat Museum: Developing a Hybrid Museum and Cultural Heritage Center in Tanjung Pura, Langkat - Isnen Fitri; Sri Hartini; Asrilia Syahfira Lubis (Journal of Environmental and Development Studies, 2025)
Museum Langkat is located in North Sumatra Province and serves as a cultural heritage site in Tanjung Pura, Langkat Regency. This museum building possesses significant architectural and historical value, with considerable potential as a cultural center due to its strategic location near other cultural heritage sites, including the Azizi mosque and the former site of the second Palace of the Sultan of Langkat. This article examines the evolution of the Langkat Museum in Tanjung Pura, North Sumatra, into a hybrid museum and cultural heritage center. The structure, formerly the administrative office of the Langkat Sultanate, currently exhibits physical decay and restricted utility. This research presents a hybrid model that combines physical restoration, digital accessibility, and community-oriented programming. The paper advocates for a sustainable and inclusive strategy to rejuvenate regional museums in Indonesia, utilizing global and regional precedents. It delineates critical research deficiencies concerning hybrid museums, community involvement, and the amalgamation of disparate cultural resources. The proposed paradigm designates the museum as a catalyst for cultural continuity, education, and regional development.